2019
DOI: 10.1186/s12935-018-0717-6
|View full text |Cite
|
Sign up to set email alerts
|

HOXB8 enhances the proliferation and metastasis of colorectal cancer cells by promoting EMT via STAT3 activation

Abstract: BackgroundPrevious studies have demonstrated that the expression of homeobox8 (HOXB8) is higher in colorectal cancer (CRC) tissues than in normal tissues; however, the precise role of HOXB8 in human CRC cells remains to be elucidated.MethodsWe generated lentiviral constructs to overexpress and silence HOXB8 in CRC cell lines, and examined their biological functions through MTT, wound healing, colony and transwell, expression of signal transducer and activator of transcription 3 (STAT3) and epithelial–mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…Moreover, STAT3 was upregulated in TGF‐β1‐induced EMT during renal fibrosis, implying that STAT3 is an innovative target for the prevention of fibrosis . Furthermore, there are many mediators that induce EMT through the activation of STAT3, such as Pin1, HOXB8, miR‐30d, and IL‐6 …”
Section: Small Molecules Against Emtmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, STAT3 was upregulated in TGF‐β1‐induced EMT during renal fibrosis, implying that STAT3 is an innovative target for the prevention of fibrosis . Furthermore, there are many mediators that induce EMT through the activation of STAT3, such as Pin1, HOXB8, miR‐30d, and IL‐6 …”
Section: Small Molecules Against Emtmentioning
confidence: 95%
“…111 Furthermore, there are many mediators that induce EMT through the activation of STAT3, such as Pin1, HOXB8, miR-30d, and IL-6. [112][113][114][115] Sepantronium bromide is an inhibitor of survivin that exhibits anticancer properties in multiple cancer types. A recent study revealed that sepantronium bromide reduced the invasion of glioblastoma induced by radiation and reversed EMT by targeting STAT3.…”
mentioning
confidence: 99%
“…JAK/STAT3 signaling also can be induced by oncoproteins, including RPL34 [125], HOXB8 [126], CD146 [127], and Akirin2 [128]. This recently recognized regulation of new oncogenes involved in activating JAK/STAT3/VEGFA, NF-κB, and ERK signaling might provide crucial targets to block the cancer progression.…”
Section: Other Proteins As Orchestratorsmentioning
confidence: 99%
“…Colorectal cancer (CRC), a common lethal tumor of the digestive tract, is the third commonly diagnosed cancer (10.2%) and the second leading cause of cancer‐related deaths in the world . Metastasis is one of the major reasons CRC patients to resume treatment . It is important to understand the mechanism of carcinogenesis and development, as CRC threaten human health and lives.…”
Section: Introductionmentioning
confidence: 99%
“…1 Metastasis is one of the major reasons CRC patients to resume treatment. 2,3 It is important to understand the mechanism of carcinogenesis and development, as CRC threaten human health and lives. Thus, elucidating the underlying mechanisms of the cause and progression of CRC is a clinical priority.…”
Section: Introductionmentioning
confidence: 99%